Pdel, Encoding a Low-Affinity cAMP Phosphodiesterase, Regulates Conidiation and Pathogenesis in Alternaria alternata Tangerine Pathotype - Lv, Weiwei; Kong, Xiangwen; Zhou, Changyong; Tang, Kezhi (Frontiers in Microbiology, 2020)
Based on intracellular second messenger cAMP, the cyclic AMP-protein kinase A (cAMP-PKA) pathway transforms extracellular stimuli to activate effectors and downstream signaling components, mediating physiological processes in filamentous fungi. The concentration of intracellular cAMP was regulated by adenylate cyclase biosynthesis and cAMP phosphodiesterase (PDEs) hydrolysis, which mediate signal transduction and termination. In this study, we used a gene deletion and complementary strategy to characterize the functions of AaPdel and AaPdeh genes, which encoded low-affinity PDEs (Pdel) and high-affinity PDEs (Pdeh) respectively, in Alternaria alternata. AaPdel, but not AaPdeh, was found to be a key regulator in conidiation and pathogenesis in A. alternata. ΔAaPdel showed defects in conidiation, producing approximately 65% reduced conidiation and forming lowly pigmented aberrant structures. In response to osmotic stress, ΔAaPdel was more sensitive to non-ionic osmotic stress than ionic osmotic stress. Moreover, AaPdel deletion mutants had defects in vegetative growth and hyphal growth. Further analyses showed that the high chitin content of ΔAaPdel might account for the sensitivity to Congo red. Based on the attenuated pathogenicity and lowly pigmented aberrant structures, the laccase activity analysis found that both AaPdel and AaPdeh were involved in laccase activity regulation. Our data further support the PKA-mediated cAMP signaling pathway, as we have found that AaPdel was involved in intracellular cAMP levels in A. alternata.